Pengaruh financial literacy, financial attitude, financial technology, self-control, dan hedonic lifestyle terhadap financial behavior - Utami, Nabila Ganes Putri; Isbanah, Yuyun (Jurnal Ilmu Manajemen, 2023)
This research aims to analyze the factors that influence the financial management behavior of the generation Z in East Java. The factors used in this study are financial literacy, financial attitude, financial technology, self-control and hedonic lifestyle. This research uses quantitative data sourced from primary data. This research population are generation Z in East Java. For the sampling technique in this study using purposive sampling and obtained 297 respondents were reached who became the samples of this research. The characteristics of respondent are gen Z, aged 17-26 years and have or used financial technology. This research analysis technique is multiple linear regression analyses and calculated with IBM SPSS 26. The results show that financial literacy and self-control can affect financial behavior. While financial attitude, financial technology, and hedonic lifestyle does not affect financial behavior. Financial literacy variables have an influence on the financial behavior because it is influences by the level of education and respondent financial literacy level was in the well literate category. Self-control positively significantly influence financial behavior because respondents have a high level of self-control, so they are able to control themselves against impulsive behavior.